1117 A Pig Model of the Preterm Neonate: Anthropometric and Physiological Characteristics. (October 2012) - Eiby, YA; Wright, LL; Lumbers, ER; Colditz, PB; Lingwood, BE
Abstract : Background and Aims: Large animal models are an essential research tool to investigate the physiology of the preterm infant, which remains poorly understood. We aim to describe the pig model of the preterm neonate in terms of growth, maturation and requirement for intensive care over a range of gestational ages and determine the effects of maternal glucocorticoid exposure and sex. Methods: Twenty-nine litters of piglets (N=305) were delivered by C-section at 91d, 94d, 97d, 100d, 104d and 113d (term 115d). Some litters received maternal betamethasone treatment (0.19mg/kg body wt; IM) at 48h and 24h prior to delivery. At 97d piglets were resuscitated, surfactant administered, and piglets were ventilated, sedated and monitored for 6–8h post-birth using standard NICU techniques. Results: At 91d, piglets were half the weight of term animals, had fused eyelids, very thin skin, no hair, and survived a maximum of 3h due to difficulties with ventilation. At 97d piglets were able to be maintained for at least 6–8h but physiology was unstable for 1–2h. Piglets 100d and older breathed spontaneously. Only near term piglets were able to maintain body temperatures. Males were heavier than females at 113d gestation (p=0.021). Exposure to maternal glucocorticoids resulted in larger females and influenced brain:body wt. Conclusions: The piglet provides a useful model of preterm neonatal physiology as very preterm piglets can be survived under standard intensive care conditions. The large litters allow for parallel experiments or the use of littermates as controls.